Parameter Optimization of Dual Clutch Transmission for an Axle-split Hybrid Electric Vehicle. Issue 5 (2019) - Cao, Xiliang; Du, Changqing; Yan, Fuwu; xu, Hongming; He, Biao; Sui, Yanfeng
Abstract: This paper reports the design optimization for a dual clutch transmission (DCT) of a multi-mode axle-split hybrid electric vehicle (HEV). The purpose of optimization is to minimize the equivalent fuel consumption of automobile power demand. The variables that need to be optimized are gear ratio and Shifting threshold value. The optimization is based on a co-simulation platform, in which, the HEV is modelled in LSM Amesim and the control/optimization algorithms are programmed in MATLAB/ Simulink. In this study, the Hybrid Particle Swarm Optimization (HPSO) algorithm is used to solve the optimization problem, which has better global and local search capability comparing with conventional PSO algorithm. The simulation results show that the optimized transmission parameters can guarantee the power demand and have a good fuel economy.